Visible-light induced photocatalytic degradation of estrone (E1) with hexagonal copper selenide nanoflakes in water - Saima Farooq (Process Safety and Environmental Protection, 2023)
Steroid hormones, being potent endocrine-disruptors, are a menace to human health and aquatic life. Herein, visible-light induced photocatalytic degradation of estrone (E1) by hexagonal copper selenide (CuSe) nanoflakes has been reported. CuSe was synthesised by a facile and low-temperature (100 oC) co-precipitation method and was characterised. The nanocrystals were of stoichiometric Cu:Se ratio with Se2- and Cu in the + 1/+ 2 mixed-valence state and exhibited laminar, flake-like morphology with a preferred hexagonal close-packed structure (P63/mmc) having average particle size and thickness of 0.229 ± 0.146 µm and 0.05 ± 0.02 µm, respectively. The adsorption isotherms of E1 were linear and the adsorption process was exothermic. The reactivity of E1 under aqueous suspensions of CuSe exposed to visible light exhibited pseudo-first-order kinetics with a rate constant, k, that varied with initial E1 concentration, light power, catalyst dose, and pH. Particularly, k was almost constant over the range pH5–9 but substantially increased as pH rose to 11, while light power and catalyst dose increased k up to a maximum, and the initial concentration reduced k. Surprisingly, CuSe oxidised E1, even in the absence of light, and leached species that were identified and their time-dependency was determined. We concluded that the disappearance of E1 by CuSe is attributed to synergetic effects of adsorption, oxidation by CuSe, and photocatalytic degradation. Supported by liquid-mass spectrometry analysis and molecular chemistry calculations, we also suggested a possible mechanism for E1 degradation. Thus, hexagonal CuSe nanocrystals can be a promising candidate for the treatment of endocrine-disrupting chemicals (EDC)-contaminated wastewaters.